Peningkatan Efektivitas Kerja Melalui Komitmen Perubahan dan Budaya Organisasi Kementerian Agama Kota Pariaman - Eldison Eldison (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2020)
The organization is a tool to achieve the goals that should be able to give clarity to one's status within the organization, both in terms of bonding, the position and role. One effort to improve the effectiveness of work is the attention to commitment, and changing organizational culture. Organizational commitment is a psychological bond for employees to the organization of the Ministry of Religious city Pariaman, willingness to work hard and the desire to maintain membership. Enhancing the ability of the organization requires organizational change with changes in system variables, strategic objectives and control systems, interpersonal relationships. In this environment there is an organization of the Ministry of Religious City Pariaman that is a culture of organizational culture, norms and practices that apply daily. Organizational commitment, organizational change, and organizational culture are the three things that are needed of the Ministry of Religiou City Pariaman on the effectiveness of the work.